2013
DOI: 10.1016/j.jtcvs.2012.03.063
|View full text |Cite
|
Sign up to set email alerts
|

How should I wean my next intra-aortic balloon pump? Differences between progressive volume weaning and rate weaning

Abstract: Intra-aortic balloon pump weaning by volume deflation allowed better hemodynamic and metabolic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…Onorati and colleagues [4] recently published an excellent study about this topic in patients with low CO. Similarly to their findings, we found a much better hemodynamic profile in animals weaned by progressive volume deflation compared with those weaned by a reduction in the assist rate, as demonstrated by the greater degree of vasodilation, the better CO and stroke volume, the fewer negative values of CCE, the higher dP/dT max , and the lower serum lactate leakage.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Onorati and colleagues [4] recently published an excellent study about this topic in patients with low CO. Similarly to their findings, we found a much better hemodynamic profile in animals weaned by progressive volume deflation compared with those weaned by a reduction in the assist rate, as demonstrated by the greater degree of vasodilation, the better CO and stroke volume, the fewer negative values of CCE, the higher dP/dT max , and the lower serum lactate leakage.…”
Section: Commentmentioning
confidence: 99%
“…Scant data exist [4] outlining optimal weaning protocols to optimize cardiocirculatory functional restoration during IABP discontinuation. Therefore, the main aim of this study was to assess changes in hemodynamics, coronary circulation, visceral flow, and biochemical markers using rate reduction or stepwise volume deflation for IABP discontinuation.…”
mentioning
confidence: 99%
“…The IABP can also be weaned by maintaining a ventricular rate of 1:1 and deflating the balloon over several hours. This leads to a decrease in the counterpulsation and a decrease in diastolic augmentation [25,26]. There are limited studies in the literature that have assessed which weaning method is superior.…”
Section: Weaning and Removalmentioning
confidence: 99%
“…prognostic factors for in-hospital mortality in the CABG patients requiring IABP (7)(8)(9)(10)(11). However, a few papers have referred to weaning protocols and withdrawal indications of IABP (12)(13)(14). We believe that prolonged balloon support is an important issue and early weaning the individuals who need longer support is of great importance, as well.…”
Section: Weaning From Iabp After Cabg Surgery: Impact Of Serum Lactatmentioning
confidence: 99%
“…Elevated serum lactate levels and lactic acidosis after cardiac surgery is an indicator of systemic hypo-perfusion and tissue hypoxia (15)(16)(17). Persistent anaerobic metabolism is an important contributor to inadequate postoperative ventricular function (14,16,17). It has also been shown that early post cardiac surgery hyperlactatemia is an independent risk factor for increase of morbidity and mortality in adults (16).…”
Section: Weaning From Iabp After Cabg Surgery: Impact Of Serum Lactatmentioning
confidence: 99%